Prospective Quantification of Tricuspid Regurgitation With Echocardiography vs 4D Flow Cardiac Magnetic Resonance - Agata Sularz, MB BChir; Ahmed S. Negm, MD; Alejandra Chavez Ponce, MD; Ahmed El Shaer, MD; Chia-Hao Liu, MD; Jared Bird, MD; Jae Oh, MD; Sorin V. Pislaru, MD, PhD; Jeremy D. Collins, MD; Mohamad Alkhouli, MD, MBA (JACC: Advances)
Background: Cardiac magnetic resonance (CMR) is a valuable tool in the assessment of valvular disease. However, its utilization in tricuspid regurgitation (TR) evaluation has been limited. Objectives: The authors sought to compare TR grading with 4D-CMR and transthoracic echocardiography (TTE). Methods: We prospectively recruited patients with ≥ moderate TR on TTE to undergo multiparametric CMR with integrated cardiac function and 4D flow assessments using a 1.5-T scanner (Siemens Somatom Aera). Patients with other severe valvulopathy, end-stage renal disease, or pacemakers were excluded. TR was graded severe on CMR when TR volume ≥45 mL and/or TR fraction ≥50%. The weighted kappa test was used to assess the agreement in overall TR grading on TTE and CMR. Results: Fifty-two patients were enrolled (mean age 78.5 ± 7.6 years, 53.8% men). The median interval between CMR and TTE was 2 days (Q1-Q3: 1-37 days). The agreement between TTE and CMR-derived TR volume was fair (kappa = 0.28, 95% CI: 0.13-0.45), with only 10 of 31 patients (32%) with ≥ severe TR on TTE meeting severe TR volume criterion on CMR (TR volume ≥45 mL). There was no agreement between TTE and CMR-derived TR fraction (kappa = 0.04, 95% CI: 0.13-0.46), with only 3 of 31 patients (13%) with ≥ severe TR on TTE meeting severe TR criterion on CMR (TR fraction ≥50%). Conclusions: Grading of TR was frequently discordant between TTE and 4D magnetic resonance imaging. Further studies are needed to elucidate the clinical impact of concordant/discordant TR grading on multimodality imaging.